KOMPARABILITAS KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL Dl INDONESIA - Fatimah, Sri Utami; Muchlis (Ibs Press, 2025)
This study was conducted to examine whether there are differences in financial performance between conventional banks and Islamic banks. The variables in this study are banking financial ratios namely LFR, LAR, ROA, ROE, BOPO or REO, NIM or NOM, CAR, NPL or NPF. This research uses descriptive statistical tests and statistical differences tests, namely non-parametric tests (mann whitney test) and is strengthened by removing outlier data and conducting parametric tests (independent sample t-test). The object of this research is the Commercial Bank in the 2014-2020 research period. There are 3 stages in this research, namely descriptive statistical tests to find out the mean value of each bank, then normality test as one of the requirements for conducting independent sample t-parametric tests. test and the last is to do statistical difference test. If the data is normally distributed, then an independent sample t-test parametric test will be carried out and if the data is not normally distributed then a non-parametric mann whitney test will be carried out. The results of this study indicate if conventional banks have better performance in the ratio of LFR, LAR,ROA, ROE, BOPO or REO, NIM or NOM and NPL or NPF. While Islamic banks have better performance in the CAR ratio. While the statistical test of Islamic banks and conventional banks has a significant difference in the ratio of ROA, BOPO or REO, NIM or NOM and NPL or NPF. And do not have a significant difference in the ratio of LFR, LAR, ROE. While there are differences in the results of conventional banks and Islamic banks CAR, the Mann Whitney test results are no differences in conventional banks and Islamic banks, while the independent sample t-test shows that there are differences between conventional banks and Islamic banks.